2021
DOI: 10.3389/fvets.2021.637716
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-2-Macroglobulin as a New Promising Biomarker Improving the Diagnostic Sensitivity of Bovine Paratuberculosis

Abstract: Johne's disease (JD) is a chronic granulomatous enteritis of ruminants caused by Mycobacterium avium subsp. paratuberculosis (MAP), which induces persistent diarrhea and cachexia. JD causes huge economic losses to the dairy industry due to reduced milk production and premature culling. Infected animals excrete MAP via feces during the prolonged subclinical stage without exhibiting any clinical signs. Therefore, accurate detection of subclinical stage animals is crucial for successful eradication of JD in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Host biomarkers have been postulated as tools to develop novel diagnostic methods for PTB. Some have been validated for detection of naturally infected cattle in various stages of Map infection. Several proteomic studies to investigate the host proteome response to mycobacterial infections and specifically to Map infection have been performed to identify biomarkers of Map infection for development of new diagnostic tools. These studies might also help to identify potential candidate genes for selective breeding programs to enhance resistance or tolerance to PTB .…”
Section: Introductionmentioning
confidence: 99%
“…Host biomarkers have been postulated as tools to develop novel diagnostic methods for PTB. Some have been validated for detection of naturally infected cattle in various stages of Map infection. Several proteomic studies to investigate the host proteome response to mycobacterial infections and specifically to Map infection have been performed to identify biomarkers of Map infection for development of new diagnostic tools. These studies might also help to identify potential candidate genes for selective breeding programs to enhance resistance or tolerance to PTB .…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that these molecules could show potential as putative biomarkers of PTB infection, especially for identification of subclinical animals showing pathological forms related to latency or resistance to the development of advance lesions. Park et al ( 89 ) identified alpha-2-macroglobulin (A2M) as a new promising biomarker improving the diagnostic sensitivity of bovine PTB. They showed that serum A2M levels were significantly higher in Map-exposed ( n = 20), subclinical shedder ( n = 27), subclinical non-shedder ( n = 50) and clinical shedder ( n = 18) groups that in the healthy control group ( n = 11, from a PTB free farm, negative by fecal PCR and IDEXX and ID Vet ELISA).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, attempts have been made to overcome the difficulty of diagnosing MAP in the subclinical stage. Differentially expressed serum proteins were identified by proteomic profiling and ELISA was performed to discover a potential novel biomarker called A2M [ 10 ]. There was also a study using the NanoString nCounter technology that suggested a combination of four miRNAs that are distinguished from the negative control group as biomarkers according to the severity of JD [ 11 ].…”
Section: Introductionmentioning
confidence: 99%